Aplikasi Teknik Swaddling, Side-Stomatch, Shushing, Swinging, Sucking(5S'S) terhadap Skala Nyeri dan Durasi Tangisan pada Neonatus Paska Prosedur Pengambilan Darah - Ning Arti Wulandari; Erni Setiyorini (STIKes Patria Husada Blitar, 2014)
Neonatal care at hospital involved many invasive procedures. The invasive procedures caused pain in neonates. The role of nurse is minimize the discomfort and pain for them. Negative effect when we let the pain in long time, there are immediately effect, short term effect and long term effect. 5Ss technique is useful to make baby comfortable and soothing neonates.The purpose of this study was to analyze the application of 5Ss technique to the pain and duration of crying neonates post blood sampling procedures. Method: Research design was experimental research with Quasi- Experimental design post test only with control group. The sample consisted of 50 neonates, 25 nonates in control group and 25 neonates in the experimental group, with inclusion criteria: aterm neonates, normal apgar score. Sampling was done by purposive sampling. The data was analyze by T-test. Result: The results showed that 5ss technique had effect to pain with p=0,000 and duration of crying, with p=0,011. The research recommended for calming crying neonates and reduce pain after invasive procedures and it is expected the results of this study can be considered for standart operating procedures for calming neonates.